Drivers of consumers’ change to an energy-efficient heating appliance (EEHA) in households - Neves, Catarina (2021)
Neves, C., & Oliveira, T. (2021). Drivers of consumers’ change to an energy-efficient heating appliance (EEHA) in households: Evidence from five European countries. Applied Energy, 298, 1-15. [117165]. https://doi.org/10.1016/j.apenergy.2021.117165